Childhood nephroblastoma in Southern and Eastern Europe and the US: Incidence variations and temporal trends by human development index. (June 2018) - Doganis, Dimitrios; Panagopoulou, Paraskevi; Tragiannidis, Athanasios; Georgakis, Marios K.; Moschovi, Maria; Polychronopoulou, Sofia; Rigatou, Efthimia; Papakonstantinou, Eugenia; Stiakaki, Eftichia; Dana, Helen; Bouka, Evdoxia; Antunes, Luis; et al.
Highlights: Incidence rates of Wilms' tumor among 12 Southern and Eastern European (SEE) countries are diverse. Overall rates in SEE countries are marginally higher than those in the USA. Median age at diagnosis was similar in SEE countries and the USA. The changes in male:female ratio of Wilms' tumor by advancement of age should be further explored. A positive association between human development index (HDI) and Wilms' tumor incidence was found. Abstract: Background: Despite advances in the management of nephroblastoma (Wilms' tumor, WT), the etiology of the tumor remains obscure. We aimed to compare nephroblastoma incidence rates and time trends among children (0–14 years) in 12 Southern and Eastern European (SEE) countries and the Surveillance, Epidemiology, and End Results Program (SEER), USA, in relation to the human development index (HDI). Methods: In total 1776 WT cases were recorded in 13 SEE collaborating registries (circa 1990–2016), whereas data on 2260 cases (1990–2012) were extracted from the SEER database. Age-standardized incidence rates (AIRs) were calculated and correlated with HDI, whereas temporal trends were evaluated using Poisson regression and Joinpoint analyses. Results: The overall SEE AIR (9.2/10 6 ) was marginally higher than that of the SEER (8.3/10 6 ), whereas significant differences were noted among the 13 SEE registries which comprised mainly Caucasian populations. A statistically significant temporal increase in incidence was noted only in Belarus. Most cases (∼75%) were diagnosed before the fifth year of life, with rates steadily declining thereafter; median age at diagnosis was similar in SEE countries and SEER. A slight male preponderance in the first year of life (male:female = 1.1) was followed by a female preponderance in the older age groups (male:female = 0.7). Lastly, a statistically significant positive association between higher HDI and increasing nephroblastoma incidence was noted (regression coefficient: +3.25, 95%CI: +1.35, +5.15). Conclusions: Variations in incidence and time trends across the examined registries, changing male-to-female patterns with advancement in age, and positive associations with the HDI imply a plausible role for environmental and genetic factors in disease etiology, and these need to be explored further.